The influence of expenditure behaviour towards homeownership / Rohayu Ab Majid ... [et al.] - Ab Majid, Rohayu; Said, Rosli; Ab Rahim, Norbaya; Basrah, Noraliza; Sahray, Kholim; Mustafar, Suriyana; Mahamood, Nur Medeena (Universiti Teknologi MARA, Perlis, 2021)
Homeownership becomes the dream of all households. It requires proper planning on the buyer's income and expenses. The different level of household expenditure often influences the allocation of money for house purchasing. Hence, various types of household expenditures have been studied to see how far they may affect the current income and homeownership. A mixed-method was adapted to completing the study. A study sample was obtained through the questionnaire survey among respondents residing within the Klang Valley region. The analysis was conducted using the correlation technique. The results show that all categories of expenditure are significant and have a high impact on the status of homeownership.